Pengaruh Kualitas Pelayanan dan Amnesti Pajak Pada Kepatuhan Wajib Pajak Orang Pribadi - Sudaarsa, Komang; Jati, I Ketut (E-Jurnal Akuntansi, 2018)
This study aims to prove empirically the influence of service quality and tax amnesty on taxpayer compliance. The population in this study was 2,591 Individual Taxpayers registered in KPP Pratama Badung Selatan who participated in the Tax Amnesty program. The sample of this research is determined by purposive sampling technique, so that there are 100 observations that meet the sample criteria. The research hypothesis was tested using multiple linear regression analysis. The results showed that the variable service quality and tax amnesty have a positive influence on taxpayer compliance. Keywords : service quality, tax amnesty, compliance